Integration of computational thinking in initial teacher training for primary schools: a systematic review - Rodrigues, Rita Neves; Costa, Cecília; Martins, Fernando (Frontiers in Education, 2024)
Computational Thinking, a capacity based on the principles of computing, has been highlighted in the specialized literature as an essential skill for the 21st century, bringing significant benefits to the problem-solving process. In this way, norms for the integration of Computational Thinking in education have emerged in the educational curricula of several countries. For this integration to be successful, it is essential that the training given to pre-service teachers enables them to develop wellplanned and structured interventions to promote the development of Computational Thinking. This article presents a systematic review of the literature that aims to investigate how the development of Computational Thinking has been integrated into teacher training. Eleven articles that corresponded to the selected research criteria were found, and the characteristics of their studies are analysed and presented in this article. The article concludes that it is necessary to invest in pre-service teacher training, highlighting the need for long-term and more comprehensive training covering not only the theoretical component but also the practical component, as well as reflection on practice.teacher training; (iii) articles that describe a training practice developed in initial teacher training; (iv) articles involving pre-service primary teachers.The following exclusion criteria were applied: (i) duplicate articles; (ii) articles published before January 1, 2014; (iii) articles in the review phase; (iv) review articles or conference proceedings; (v) articles that did not focus on the development of Computational Thinking in initial primary teacher training; (vi) articles that did not describe a training practice developed in initial teacher training; (vii) articles that do not involve pre-service primary teachers.